PERKEMBANGAN SPIRITUAL REMAJA SMA DHARMA PUTRA - Saputra, Denny Surya (Jurnal Psikologi : Media Ilmiah Psikologi, 2018)
AbstractBased on the experience of researchers as school counselors in Dharma Putra Tangerang High School, researchers saw that the development of youth spirituality in Dharma Putra High School, specifically in terms of religious / faith development became an important need for adolescents to develop healthy and accepted behavior in their environment. Therefore, the development of spirituality has an important role for the lives of adolescents. The purpose of this study is to find out the description of the dominant stages in the development of adolescent spirituality in Dharma Putra High School, Tangerang. The population in this study were adolescents in SMA Dharma Putra Tangerang with a total sample of 30 students. The research method used is descriptive quantitative method. The results showed that the spiritual development of adolescent Dharma Putra High School was dominated by stage 3 with indicators reviewing the correctness of wrong behavior through consideration of teenagers based on what others would say by 23%.Â Keyword: youth, development of spiritualityÂ AbstrakBerdasarkan pengalaman peneliti sebagai konselor sekolah di SMA Dharma Putra Tangerang, peneliti melihat bahwa perkembangan spiritualitas remaja di SMA Dharma Putra, secara khusus dalam hal perkembangan agama/iman menjadi satu kebutuhan penting untuk remaja dapat mengembangkan perilaku yang sehat dan diterima oleh lingkungannya. Oleh karena itu, perkembangan spiritualitas memiliki peranan yang penting bagi kehidupan remaja. Tujuan dari penelitian ini yaitu untuk mengetahui gambaran tahap yang dominan pada perkembangan spiritualitas remaja di SMA Dharma Putra, Tangerang.Populasi dalam penelitian ini adalah remaja di SMA Dharma Putra Tangerang dengan jumlah sampel dalam penelitian ini adalah berjumlah 30 siswa. Metode penelitian yang dilakukan adalah metode deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa Perkembangan spiritual remaja SMA Dharma Putra didominasi oleh tahap 3 dengan indikator meninjau benar salahnya perilaku melalui pertimbangan remaja berdasarkan apa yang akan dikatakan oleh orang lain sebesar 23%.Â Kata kunci: remaja, perkembangan spiritualitas.